Effects of posture and body mass index on body girth assessment - Sousa, Ana Sofia (2016)
Background: The present study aimed to evaluate the effect of posture on body girth assessment among hospitalized adults and older adults. We further explored the influence of body mass index (BMI) on this effect. Materials and Methods: A cross-sectional study was conducted among hospitalized adult patients. Arm, waist, hip, and calf girths were obtained for each patient in standing and supine positions. Body girths were obtained in the 2 body positions, and differences were compared according to BMI normal-weight and overweight categories. Results: In total, 123 patients (27.6% aged 65 years) composed the study sample. Significant differences were found between measurements obtained in standing and supine positions, ranging from 0.6-1.1 cm. Intraclass correlation coefficient (ICC) values were 0.97, and agreement ranged from 81.3%-87% (weighted 0.84). Similar results were found when differences were stratified by BMI categories. Conclusion: Although body girth assessment in standing and supine positions in hospitalized adults and older adults differs, these differences are small and are not dependent on BMI categories.